Smart specialisation : opportunities and challenges for regional innovation policy - Foray, Dominique (Routledge, 2015)
"This book provides the first full analysis of smart specialisation strategies both at theoretical and practical levels. As a new policy approach smart specialisation has already been widely adopted in Europe and beyond. Smart Specialisation: Opportunities and Challenges for Regional Innovation Policy analyses the concept of smart specialisation, discusses the need for smart specialisation strategies, explains how the approach varies from standard policy processes and explores the necessary conditions for successful implementation.This book has been written at a critical period of the implementation of smart specialisation strategies across Europe. As the EU has adopted smart specialisation as a mandatory principle for every region and member state this book will be useful to policy makers in regional and national administrations in Europe, policy makers in other parts of the world, consultants, analysts and experts active on the "markets for smart specialisation diagnosis and expertise" as well as scholars, researchers and graduate students working in the field of regional studies, technology policy and geography of innovation"--Resumé vydavatele
Keywords: regionální politika; regionální rozvoj; regionální ekonomie; inovace; regional policy; regional development; regional economics; innovations; monografie; monographs